ESRA19-0412 Continuous spinal anaesthesia with levobupivacaine in a patient with severe aortic stenosis undergoing distal ureterectomy with ureteral reimplantation. (30th August 2019) - Fernandes, A; Lopes, L
Abstract : Background and aims: Severe aortic stenosis (SAS) is associated with increased morbidity and mortality during the perioperative period in patients undergoing noncardiac surgery. Continuous spinal anaesthesia (CSA) may prove advantageous in this subgroup of patients, to minimize hemodynamic changes. We report a case that illustrates the application of this technique. Methods: An 88-year-old woman with a history of SAS (submitted to balloon aortic valvuloplasty 1 month prior), stage 4 chronic kidney disease, hypertension, type 2 diabetes and dyslipidemia was proposed for distal ureterectomy with ureteral reimplantation due to urothelial carcinoma. After standard ASA monitoring, premedication (1 mg midazolam IV) and placement of an arterial line, dural puncture at L3-L4 spinal level was performed using a 18G Tuohy needle, and the catheter introduced intrathecally. 2 µg of sufentanyl and 2.5 mg of levobupivacaine (0.5%) were given through the catheter. After the initial dose, additional top-ups of levobupivacaine 0.1% were administered (total 4 mg). The spinal catheter was removed at the end of surgery. IV fentanyl (total 100 µg) was given in intermittent boluses throughout. During the surgical procedure, which lasted approximately 3 hours, a peripheral noradrenaline infusion up to 8 mcg/min to maintain MAP values above 65 mmHg was used. Results: The patient remained stable throughout surgery and spent the first 48h of postoperative recovery in the coronary intensive care unit. The postoperative course was uneventful, and the patient was discharged on the 10th postoperative day. Conclusions: CSA, although unpopular, is a safe and effective anesthetic technique for the management of patients with SAS.